Obesity in children A review (Bangladesh Medical Journal, 2014)
Childhood obesity is now among the most widespread medical problems affecting children and adolescents living in both developed and developing countries. Approximately 21-24% of children and adolescents are overweight, and another 16-18% is obese. The prevalence of obesity is increasing in all pediatric age groups, in both sexes, and in various ethnic and racial groups. Many factors, including genetics, environment, metabolism, lifestyle, and eating habits, are believed to play a role in the development of obesity. However, more than 90% of cases are idiopathic; less than 10% are associated with hormonal or genetic causes. Obesity has a profound effect on a patient's life. Childhood obesity predisposes to insulin resistance and type 2 diabetes, hypertension, hyperlipidemia, liver and renal disease, and reproductive dysfunction. This condition also increases the risk of adult-onset obesity, cardiovascular disease and can create emotional and social problems. Therefore, the prevention and treatment of obesity have emerged as a challenge to the pediatric practitioner. DOI: http://dx.doi.org/10.3329/bmj.v42i3.19004 Bangladesh Med J. 2013 Sept; 42 (3): 92-96